2022
DOI: 10.14202/vetworld.2022.2575-2586
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and chemical evaluation of dairy products commercialized in the Lebanese market

Abstract: Background and Aim: Cheese is considered an essential component of the Lebanese table, however, several foodborne illnesses have been reported due to cheese consumption. This study aimed to assess the microbiological quality and the occurrence of antibiotic and pesticide residues in two traditional Lebanese cheeses, Akkawi and Baladiyeh. In addition, drug resistance of isolated pathogens from the cheese samples was evaluated. Materials and Methods: Fifty Akkawi and Baladiyeh cheese samples were obtained in du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…We also found that 80% of the cheese samples would be rejected (deemed unacceptable for human consumption) based on the E. coli densities and LIBNOR standards (2002:223 and 2003:495), while up to 32% of the samples would be rejected based on S. aureus densities ( Figure 1 ). Therefore, this study reported higher non-conformity rates in comparison to the limited studies available on dairy products in Lebanon [ 14 , 21 ]. Beyond the use of bacterial indicators, it is known that the enterotoxins secreted by S. aureus can cause gastrointestinal disease [ 9 ].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…We also found that 80% of the cheese samples would be rejected (deemed unacceptable for human consumption) based on the E. coli densities and LIBNOR standards (2002:223 and 2003:495), while up to 32% of the samples would be rejected based on S. aureus densities ( Figure 1 ). Therefore, this study reported higher non-conformity rates in comparison to the limited studies available on dairy products in Lebanon [ 14 , 21 ]. Beyond the use of bacterial indicators, it is known that the enterotoxins secreted by S. aureus can cause gastrointestinal disease [ 9 ].…”
Section: Discussionmentioning
confidence: 61%
“…The high prevalence of MDR E. coli in Akkawi cheese was not surprising ( Figure 2 and Figure 3 ; Table 1 ), because several studies have reported a widespread antibiotic resistance in the Lebanese community, as well as in environmental and food matrices [ 29 , 34 , 35 , 37 , 38 , 39 , 46 ]. A recent study on dairy products in Lebanon screened 29 E. coli isolates that were found to be resistant to AMC (69% of isolates), CFM (11%), CHL (31%), and STR (100%), and all the tested isolates were multidrug-resistant [ 21 ]. However, in the aforementioned study, the number of E. coli isolates (n = 29) and antibiotics tested was very limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data obtained were interpreted in accordance with EUCAST 2021 (EUCAST, 2021) and Clinical and Laboratory Standards Institute (CLSI) 2019 (CLSI, 2019). Isolates of bacteria that are resistant to at least three classes of antibiotics have been classified as multidrug-resistant microorganisms [ 24 ].…”
Section: Methodsmentioning
confidence: 99%